Association between neutrophil-percentage-to-albumin ratio and periodontitis: insights from a population-based study - Zheng, Ziyang; Xie, Xinyu; Wang, Lan; Xu, Mingzhang; He, Jiaqi; Deng, Yunyi; Yu, Ke (Frontiers in Nutrition, 2025)
BackgroundPeriodontal diseases, characterized by the loss of tooth-supporting structures, are highly prevalent in the general population. The Neutrophil-Percentage-To-Albumin Ratio (NPAR) has been identified as a promising biomarker for systemic inflammation, but its relationship with periodontal disease has not been thoroughly investigated. Despite growing interest in its role in other chronic conditions, the specific connection between NPAR and periodontal disease remains underexplored and requires further examination to understand its potential clinical applications.MethodsA population-based analysis was performed using data from the National Health and Nutrition Examination Survey (NHANES), with a total of 8,389 participants included with complete full-mouth periodontal examination, NPAR related index and covariates. NPAR was employed as the primary independent variable, the periodontitis and clinical periodontal parameters were set to the outcomes along with tooth counts and functional dentition as the sensitivity outcomes. To investigate its association between NPAR and periodontitis, weighted multivariate linear and logistic regression analyses were conducted. Sensitivity and replication analyses were also carried out to assess the robustness and reliability of the findings.ResultsThis population-based study revealed a significant association between elevated NPAR levels and a higher likelihood of periodontitis, increased attachment loss (AL), and probing depth (PD). After full adjustment for potential confounders, NPAR was significantly associated with periodontitis (OR = 1.04, p = 0.005), attachment loss (β = 0.03, p < 0.001), and probing depth (β = 0.02, p < 0.001). Furthermore, the highest quartile of NPAR remained significantly associated with periodontitis (OR = 1.34, p = 0.010), AL (β = 0.15, p < 0.001) and PD (β = 0.09, p < 0.001). A significant trend was observed, with periodontitis strongly associated with increasing NPAR levels. These findings were further validated by the sensitivity analyses with decreased tooth counts (β = −0.08, p < 0.005) and the lower incidence of functional dentition (OR = 0.96, p = 0.030). Additionally, the replication analysis also enhanced the roundness of the results (OR = 1.07, p < 0.001).ConclusionThis population-based study demonstrated a statistically significant positive relationship between NPAR and the prevalence of periodontitis, NPAR has been recognized as a potential biomarker for periodontal disease. Additional longitudinal research are needed to confirm these findings and investigate the clinical implications of NPAR in managing periodontal conditions.